Co-expression of IL-15 and CCL21 strengthens CAR-NK cells to eliminate tumors in concert with T cells and equips them with PI3K/AKT/mTOR signal signature - Jie Zhou; Lu Tang; Yu Hu; Jun Deng; Yingying Li; Wei Xiong; Jianghua Wu; Jia Xu; Wenjing Luo; Heng Mei; Xindi Wang; Zhaozhao Chen; et al. (Journal for ImmunoTherapy of Cancer)
Background Chimeric antigen receptor (CAR)-natural killer (NK) cell therapy has demonstrated safety and feasibility in clinical settings; however, limited efficacy due to intrinsic dysfunction and extrinsic suppression remains an unresolved issue. T cells provide multifaceted support to NK cell-mediated responses. Here, we aimed to design a novel CD19-targeted CAR-NK, engineered with secreted interleukin-15 and C-C motif chemokine ligand 21 (ie, 15×21 CAR-NK), capable of recruiting and cooperating with T cells.Methods We characterized 15×21 CAR-NK cells by performing experiments in vitro and in mouse models, and conducting RNA sequencing.Results 15×21 CAR-NK cells exhibit strong capabilities in cytotoxicity, cytokine production, effector molecule expression, and T-cell recruitment in vitro. Cooperation with T cells promoted efficient tumor-cell elimination, alleviated mutual exhaustion phenotypes, and enhanced the expression of effector molecules/receptors. The recruitment and cooperative effects also result in effective tumor control in mouse models. In addition, 15×21 CAR-NK cells strongly enrich the phosphatidylinositol 3-kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) pathway - a key intracellular signaling cascade that is associated with enhanced downstream pro-survival signaling, anti-apoptotic ability, mitochondrial function, and cytotoxicity.Conclusions Our study highlights the intrinsic advantages and extrinsic T-cell cooperative benefits of 15×21 CAR-NK cells, providing a promising strategy for NK-cell-based immunotherapy.